Does botulinum toxin A improve the walking pattern in children with idiopathic toe-walking? - Engström, Pähr (Springer Berlin Heidelberg, 2010)
BACKGROUND: Numerous recommendations have been made for treating idiopathic toe-walking (ITW), but the treatment results have been questioned. The purpose of this study was to investigate whether botulinum toxin A (BTX) improves the walking pattern in ITW as examined with 3-D gait analysis. PARTICIPANTS AND METHODS: A consecutive series of 15 children (aged 5–13 years) were enrolled in the study. The children underwent a 3-D gait analysis prior to treatment with a total of 6 units/kg bodyweight Botox(®) in the calf muscles and an exercise program. The gait analysis was repeated 3 weeks and 3, 6, and 12 months after treatment. A classification of toe-walking severity was made before treatment and after 12 months. The parents rated the perceived amount of toe-walking prior to treatment and 6 and 12 months after treatment. RESULTS: Eleven children completed the 12-month follow-up. The gait analysis results displayed a significant improvement, indicating decreased plantarflexion angle at initial contact and during swing phase and increased dorsiflexion angle during midstance at all post-treatment testing instances. According to the parents’ perception of toe-walking, 3/11 children followed for 12 months had ceased toe-walking completely, 4/11 decreased toe-walking, and 4/11 continued toe-walking. After 6–12 months, the toe-walking severity classification improved in 9 of the 14 children for whom data could be assessed. CONCLUSIONS: A single injection of BTX in combination with an exercise program can improve the walking pattern in children with ITW seen at gait analysis, but the obvious goal of ceasing toe-walking is only occasionally reached.